PEMBINAAN KARIR TENAGA KEPENDIDIKAN DI SMK NUSATAMA PADANG - Berliana Tamim; Hasnawati Hasnawati (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine how career coaching/development, factors that influence career coaching/development, and obstacles in career coaching/development. The research method used is qualitative. The data sources that were determined were the principal, the head of the administrative staff and all education staff employees. Data collection techniques through interviews and documentation. The results showed that the implementation of coaching/career development for education staff at SMK Nusatama Padang has been going well but still not optimal. The placement of educational staff's work positions is in accordance with the abilities of each employee. The coaching/career development of education staff at SMK Nusatama Padang is still not optimal because the number of employees tends to be small so that the career development of education staff is hampered. The obstacle in career development is that several plans have not been achieved. Therefore, the principal carries out career coaching for employees and education staff by holding career coaching training every year so that the career development planning process at SMK Nusatama Padang runs optimally.